The Role of the Constitutional Court as a Stimulator of the Amendment of Traffic and Road Transport Act - Wijayanti, Winda; Putri, Mery Christian; Sabila, Sharfina (Jurnal Dinamika Hukum, 2021)
There is a huge increase in the number of road traffic accidents by underage vehicle drivers. They should not be in the highway, therefore it becomes parent’s obligation to watch their activity. However, they often ride vehicles in a highway that may cause road accidents that takes victims. It seems to be an unjust condition for other citizens who have been obedient in using highways. Indonesia’s Constitutional Court has the judicial review authority and has examined the Act Number 22 Year 2009 concerning Traffic and Road Transport for 13 times, somehow there is only one article that is cancelled by the Court. This Act has been implemented for 11 years and never been revised. The Decision Number 15/PUU-XVIII/2020 denied the applicant’s in challenging the Act but the court is limited as the stimulator of regulation revision that becomes the authority of legislator. This article will analyze the Constitutional Court Decision as the consideration for legislator to provide justice for every road user and elaborate the Court Decision with the existing regulation regarding road traffics to bring benefits for legislation making in the future. The Constitutional Court must have become the stimulator for legislator since the authority is limited.Keywords- stimulator; the amendment of act; the role of the Constitutional Court; traffic and road transport act